2021
DOI: 10.1088/1755-1315/890/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

Increasing growth and survival rate of tilapia larvae (Oreochromis niloticus) by adding polychaeta Nereis sp dry meal into feed formulation

Abstract: Aquaculture has been known as one of solutions in dealing with food security problem through applying best practices of aquaculture and increasing fish production. In many countries, fish production is considered an essential activity contributing to household income and trade. However, fish feed has an expensive price, and it constitutes 60-70% total cost of production. The objective of this study is to reveal an alternative cheap source for additional ingredients to fish diet formulation of Tilapia larvae (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Moreover, the inclusion of 40% PM dietary protein from Nereis sp. promoted the growth and survival of tilapia larvae ( Oreochromis niloticus ), supporting this ingredient as a suitable alternative protein source in aquafeeds ( 46 ). Furthermore, a recent study by Kals et al.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, the inclusion of 40% PM dietary protein from Nereis sp. promoted the growth and survival of tilapia larvae ( Oreochromis niloticus ), supporting this ingredient as a suitable alternative protein source in aquafeeds ( 46 ). Furthermore, a recent study by Kals et al.…”
Section: Discussionmentioning
confidence: 92%
“…Final length mainly for treatment A (2.84±0.11 mm) was suitable size for stocked in pond and SGR relatively higher compared with larvae fed that contained polychaeta (Nereis sp.) meal into the diet [37]. A study on higher fry density up to 30 fish Lhave been reported, however salinity media still low and maximum 2 ppt [10].…”
Section: Water Qualitymentioning
confidence: 98%
“…] Where: F: the amount of feed consumed Wt: fish biomass at the end of the study (g) W0: fish biomass at the beginning of the study (g) d: Biomass of fish which died during the study (g) Survival rate (%) is defined as the ratio between the number of fish harvested and the fish stocked during the rearing period and is calculated by the formula [10]:…”
Section: Growth Performance Survival Rate and Feed Efficiencymentioning
confidence: 99%